Cloning and expression of a gene encoding an integrin-like protein in Candida albicans. - Gale, C (1996)
The existence of integrin-like proteins in Candida albicans has been postulated because monoclonal antibodies to the leukocyte integrins alpha M and alpha X bind to blastospores and germ tubes, recognize a candidal surface protein of approximately 185 kDa, and inhibit candidal adhesion to human epithelium. The gene alpha INT1 was isolated from a library of C. albicans genomic DNA by screening with a cDNA probe from the transmembrane domain of human alpha M. The predicted polypeptide (alpha Int1p) of 188 kDa contains several motifs common to alpha M and alpha X: a putative I domain, two EF-hand divalent cation-binding sites, a transmembrane domain, and a cytoplasmic tail with a single tyrosine residue. An internal RGD tripeptide is also present. Binding of anti-peptide antibodies raised to potential extracellular domains of alpha Int1p confirms surface localization in C. albicans blastopores. By Southern blotting, alpha INT1 is unique to C. albicans. Expression of alpha INT1 under control of a galactose-inducible promoter led to the production of germ tubes in haploid Saccharomyces cerevisiae and in the corresponding ste12 mutant. Germ tubes were not observed in haploid yeast transformed with vector alone, in transformants expressing a galactose-inducible gene from Chlamydomonas, or in transformants grown in the presence of glucose or raffinose. Transformants producing alpha Int1p bound an anti-alpha M monoclonal antibody and exhibited enhanced aggregation. Studies of alpha Int1p reveal novel roles for primitive integrin-like proteins in adhesion and in STE12-independent morphogenesis.